Timber gridshells: Numerical simulation, design and construction of a full scale structure. (August 2015) - D'Amico, B.; Kermani, A.; Zhang, H.; Pugnale, A.; Colabella, S.; Pone, S.
Abstract: Timber gridshell structures, such as the Multihalle for the federal garden festival in Mannheim or the Downland Museum, have been the result of a creative–generative process that indissolubly 'welded' the structural contribution to that of form exploration. The challenging design and construction issues have been typically addressed and resolved in several inventive ways. However, still now, form-finding and erection of timber gridshells present many difficulties. In this regard, this paper aims to provide a series of novel steps to address some of the main design and construction issues that are associated with 'actively-bent' timber gridshell structures. First, the main characteristics of the construction process of timber gridshells are described and the basic theoretical concepts for its numerical simulation, through Dynamic Relaxation method, are introduced. Second, a practical method for sizing the laths' cross-section is presented. Third, a new erection technique for timber gridshells is proposed and applied to the construction of a full scale (prototype) structure, the Toledo gridshell 2.0. Fourth, a new bracing system for the same structure, which was built at the Faculty of Architecture, University of Naples Federico II in June–July 2014, is explained and discussed. The paper also highlights the need for further application to validate the techniques explained here, with particular attention being paid for the construction of large scale free-form structures.